Quality Assurance of Dose Distribution of Photon Beam Planning by Anisotropic Analytical Algorithm (AAA) - Alam, M Jahangir; Hussain, Syed Md Akram; Afroj, Kamila; Shrivastava, Shyam Kishore (Bangladesh Journal of Medical Physics, 2013)
A three dimensional treatment planning system has been installed in the Oncology Center, Bangladesh. This system is based on the Anisotropic Analytical Algorithm (AAA). The aim of this study is to verify the validity of photon dose distribution which is calculated by this treatment planning system by comparing it with measured photon beam data in real water phantom. To do this verification, a quality assurance program, consisting of six tests, was performed. In this program, both the calculated output factors and dose at different conditions were compared with the measurement. As a result of that comparison, we found that the calculated output factor was in excellent agreement with the measured factors. Doses at depths beyond the depth of maximum dose calculated on-axis or off-axis in both the fields or penumbra region were found in good agreement with the measured dose under all conditions of energy, SSD and field size, for open and wedged fields. In the build up region, calculated and measured doses only agree (with a difference 2.0%) for field sizes > 5 × 5 cm2 up to 25 × 25 cm2. For smaller fields, the difference was higher than 2.0% because of the difficulty in dosimetry in that region. Dose calculation using treatment planning system based on the Anisotropic Analytical Algorithm (AAA) is accurate enough for clinical use except when calculating dose at depths above maximum dose for small field size. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14686 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 43-49